2008
DOI: 10.1105/tpc.107.057612
|View full text |Cite
|
Sign up to set email alerts
|

Calmodulin7 Plays an Important Role as Transcriptional Regulator inArabidopsisSeedling Development

Abstract: Although calmodulin (CaM) is known to play multiple regulatory roles in eukaryotes, its direct function as transcriptional regulator is unknown. Furthermore, the physiological functions of CaM are largely unknown in plants. Here, we show that one of the four Arabidopsis thaliana CaM isoforms, CAM7, is a transcriptional regulator that directly interacts with the promoters of light-inducible genes and promotes photomorphogenesis. CAM7 overexpression causes hyperphotomorphogenic growth and an increase in the expr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

7
146
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
6
2

Relationship

5
3

Authors

Journals

citations
Cited by 113 publications
(153 citation statements)
references
References 45 publications
7
146
0
Order By: Relevance
“…Furthermore, although hyh mutants do not display any morphological defects in WL (23), the hypocotyl length of gbf1 hyh double mutants indicates that hyh partially suppresses the phenotype of gbf1 mutants in WL. Such redundant functional relationships have also been observed with HY5 and CAM7 (14). Furthermore, BL-mediated induction of RBCS-1A was also found to be antagonistically regulated by GBF1 and HY5 or HYH.…”
Section: Discussionmentioning
confidence: 55%
See 1 more Smart Citation
“…Furthermore, although hyh mutants do not display any morphological defects in WL (23), the hypocotyl length of gbf1 hyh double mutants indicates that hyh partially suppresses the phenotype of gbf1 mutants in WL. Such redundant functional relationships have also been observed with HY5 and CAM7 (14). Furthermore, BL-mediated induction of RBCS-1A was also found to be antagonistically regulated by GBF1 and HY5 or HYH.…”
Section: Discussionmentioning
confidence: 55%
“…So far, HY5 and CAM7/ZBF3 are two positive regulators known of light signaling pathways that act downstream of multiple photoreceptors, including phytochromes and cryptochromes (5,(12)(13)(14). HY5 has been genetically defined as a positive regulator of photomorphogenesis based on its partially etiolated phenotype in light-grown mutant seedlings (15)(16)(17)(18).…”
mentioning
confidence: 99%
“…The coimmunoprecipitated genomic DNA fragments with MYC2-cMyc were analyzed by real-time PCR. The amount of DNA fragment of the SPA1 promoter coimmunoprecipitated from the transgenic seedlings was found to be about 12-fold enriched as compared with the overexpresser cMyc-CAM7 transgenic seedlings (used as a control; Kushwaha et al, 2008;Fig. 1C).…”
Section: Myc2mentioning
confidence: 99%
“…Although the molecular and physiological functions of calmodulin (CaM) remain largely unknown in plants, various studies suggest that Ca 2+ /CaM is involved in light-mediated seedling development and gene expression. Detailed mutational, transgenic, and physiological studies have recently demonstrated that HY5 and CAM7 function in a synergistic or additive manner to promote photomorphogenic growth and lightregulated gene expression (Kushwaha et al, 2008).…”
mentioning
confidence: 99%
“…In Arabidopsis, only two members of this gene family have been functionally characterized, CAM3 (Zhang et al 2009) and CAM7 (Kushwaha et al 2008).…”
Section: Introductionmentioning
confidence: 99%